Charged jet evolution and the underlying event in proton-antiproton collisions at 1.8 TeV - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
The growth and development of "charged particle jets" produced in proton-antiproton collisions at 1.8 TeV are studied over a transverse momentum range from 0.5 GeV/c to 50 GeV/c. A variety of leading (highest transverse momentum) charged jet observables are compared with the QCD Monte Carlo models HERWIG, ISAJET, and PYTHIA. The models describe fairly well the multiplicity distribution of charged particles within the leading charged jet, the size of the leading charged jet, the radial distribution of charged particles and transverse momentum around the leading charged jet direction, and the momentum distribution of charged particles within the leading charged jet. The direction of the leading "charged particle jet" in each event is used to define three regions of η-φ space. The "toward" region contains the leading "charged particle jet," while the "away" region, on the average, contains the away-side jet. The "transverse" region is perpendicular to the plane of the hard 2-to-2 scattering and is very sensitive to the "underlying event" component of the QCD Monte Carlo models. HERWIG, ISAJET, and PYTHIA with their default parameters do not describe correctly all the properties of the "transverse" region.